EXTRAORDINARY CAPACITY FOR THE LARVAL BIOCONTROL OF MOSQUITOES IN THE SPECIES GAMBUSIA PUNCTATA, POEY, 1854 - Argota-Pérez, George (2021)
The larval control of mosquitoes continues to be a priority for health authorities and despite the application of bioregulation for several decades, biological control seems to be unknown as a sustainable tool. The objective of the note to the editor was to indicate the extraordinary capacity for the larval biocontrol of mosquitoes in the species Gambusia punctata Poey, 1854. Yes, under natural conditions of contamination G. punctata shows its predatory effectiveness of mosquito larvae, then in those places that such contamination can be reversible, why is a chemical control applied to quickly supply this natural response, since science has recognized some positive effects of larvicides, but in the same way, the consequences not only affect the environment where it lives G. punctata, but to human health itself when exposed to water resources contaminated with non-natural products.